1984
DOI: 10.1148/radiology.153.3.6494459
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular calcifications in association with intra-articular corticosteroid injections.

Abstract: The authors report on three patients who received intra-articular corticosteroid injections (IACI) in the small joints of their hands for the symptomatic relief of local inflammation. In these cases radiographs showed that among the complications of IACI are periarticular soft-tissue calcifications. Evidence suggests that these calcifications are composed of hydroxyapatite crystals, which may themselves produce inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Further, reports based on aspiration of periarticular calcifications resulting from IAS have suggested that the periarticular calcifications associated with steroid injections are hydroxyapatite crystals resulting from tissue necrosis from steroid leakage into soft tissue, and it has been hypothesized that these crystals themselves can induce a localized inflammatory arthritis 21 . In addition, an animal model of TMJ growth and repair indicated that experimentally induced mandibular shift may stimulate new bone formation within the contralateral condyle as a mechanism of repair 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, reports based on aspiration of periarticular calcifications resulting from IAS have suggested that the periarticular calcifications associated with steroid injections are hydroxyapatite crystals resulting from tissue necrosis from steroid leakage into soft tissue, and it has been hypothesized that these crystals themselves can induce a localized inflammatory arthritis 21 . In addition, an animal model of TMJ growth and repair indicated that experimentally induced mandibular shift may stimulate new bone formation within the contralateral condyle as a mechanism of repair 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Periarticular calcification is known to be associated with the use of triamcinolone hexacetonide and prednisone. [17][18][19] We are aware of only two studies which have explored the rate of success in injection of the ankle. Lopes et al 14 in a recent clinical study in patients with rheumatoid arthritis showed that 77% of injections were intra-articular in 54 ankles, although it was unclear which technique had been used.…”
Section: Discussionmentioning
confidence: 99%
“…Gerster and Fallet 15 described four cases of peri-articular calcification related to injection of corticosteroid into the small joints of the hands, and such changes are known to be caused by triamcinolone hexacetonide and by prednisone in particular. 4,16,17 Several studies in vivo and in animal experiments have described the effects of local corticosteroid injection on tendons such as tendon rupture and reduced strength of bony attachment of ligaments. 5,6,18,19 Diagnostic injections of acromioclavicular joints are carried out frequently and an unintended periarticular injection, giving no benefit, may possibly lead to a misinterpretation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Serious complications following unintentional periarticular injection of corticosteroid are well documented as far as major joints and those of the fingers are concerned. [4][5][6] However, only a few reports exist regarding the frequency of unintentional peri-articular injections in acromioclavicular joint. 7,8 The objectives of this study were to estimate the overall frequency of peri-articular injections using a cadaver model, to investigate the degree to which experience contributes to successful injection of the joint and to compare the results using an image intensifier.…”
mentioning
confidence: 99%